PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK DIGITAL BERBASIS NYANYIAN ANAK PADA MATERI KERAGAMAN BUDAYA DI JAWA TIMUR KELAS V SDN KENITEN 1 - Devina (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2026)
This research is motivated by the low understanding of fifth-grade students of SDN Keniten 1 regarding the material of cultural diversity in East Java. The results of observations and interviews show that 57% of students have not achieved the Learning Objective Achievement Criteria (KKTP) set. This condition is influenced by the use of learning media that is less varied so that learning tends to be monotonous and less interesting. This study aims to develop a Digital Flipbook based on children's songs that is feasible, practical, and effective for use in science learning on cultural diversity in East Java for fifth-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. The research subjects include material experts, media experts, fifth-grade teachers, and fifth-grade students of SDN Keniten 1 Mojo. The limited trial involved 7 students, while the extensive trial involved 14 students. Data collection techniques used include observation, interviews, questionnaires, pre-tests, post-tests, and documentation. Qualitative data were analyzed through data reduction, data presentation, and conclusion drawing, while quantitative data were analyzed using percentage calculations. The results showed that the Digital Flipbook based on children's songs obtained a validity level of 90% with a very valid category, which consisted of media expert validation of 80% and material expert validation of 100%. The level of practicality based on teacher responses reached 88%, while student responses reached 92% in limited trials and 95% in extensive trials with a very practical category. The results of the effectiveness test showed classical learning completion of 85% in both limited and extensive trials, so it is included in the very effective category. Based on these results, it can be concluded that the Digital Flipbook based on children's songs developed meets the criteria of validity, practicality, and effectiveness for use in science learning on cultural diversity in East Java. This media can be used as an alternative learning that is innovative, interesting, interactive, and able to improve students' understanding of regional cultural diversity.